Correlation among Mother Tongue, Socio-Economic Status and Academic Performance of Social Studies Students - Okpomoh, Avwerosuoghene Princess; Peter, Dania Ogbianugene; Clifford , Ogheneakoke Edore (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study investigated the relationship among mother tongue (Urhobo language), socio-economic status, and the academic performance of social studies students in upper basic schools in Delta State. The study focused on one independent variable, mother tongue (Urhobo language instruction), while academic performance was the dependent variable, and socioeconomic status was adopted as a moderating variable. A quasi-experimental pre-test post-test control group design was the research design. The population comprised 80,912 Upper Basic 8 Social Studies students in Delta State during the 2023/2024 academic session. A sample of 100 students was selected using multistage, purposive, and random sampling techniques. One school was used as the experimental group, receiving instructions in the Urhobo language, while the control group was taught in the English language. Data was collected using a Social Studies Mother Tongue Test (SSMTT), which had a reliability coefficient of 0.89. Research questions were answered using descriptive statistics, while hypotheses were tested using a t-test at a 0.05 level of significance. The findings revealed that students taught social studies with their mother tongue performed significantly better than those taught with English, demonstrating that mother-tongue instruction enhances comprehension, retention, and engagement. Additionally, socio-economic status did not moderate the relationship between mother tongue and academic performance of students, suggesting that language familiarity is more influential than financial status. The study recommended policy initiatives, promoting indigenous language instruction, and increased parental support for mother-tongue learning. These findings contribute to educational research by reinforcing the cognitive advantages of using mother tongue for teaching and its potential for improving learning outcomes across socioeconomic groups.